Ionic liquids: new materials with wide applications - Khupse, Nageshwar D.; Kumar, Anil (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2010)
Ionic liquids have emerged as possible substitutes for volatile organic solvents and have found many applications in a variety of research areas. In this review, an effort has been made to discuss the special properties of ionic liquids that render these unique solvent media useful in chemical transformations, electrochemical applications, extractions, etc.
Keywords: Chemical processes; Electrochemical devices; ionic liquids; Physicochemical properties; Solvent properties; viscosity